2021
DOI: 10.1186/s12875-021-01601-x
|View full text |Cite
|
Sign up to set email alerts
|

Prerequisites for providing effective support to family caregivers within the primary care setting – results of a study series in Germany

Abstract: Background General Practitioners are considered to be well placed to monitor home-care settings and to respond specifically to family caregivers. To do this, they must be sensitive to the needs and expectations of caregivers. In order to determine the current status of GP care in terms of the support given to family caregivers, a series of studies were conducted to gather the perspectives of both caregivers and GPs. The results are used to derive starting points as to which measures would be se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 58 publications
1
11
0
Order By: Relevance
“…This hesitance sometimes leads to problematical situations. The results from these interviews match those of other studies, which showed that early and systematic identification of family carers remains challenging in the daily general practice setting 8 14…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…This hesitance sometimes leads to problematical situations. The results from these interviews match those of other studies, which showed that early and systematic identification of family carers remains challenging in the daily general practice setting 8 14…”
Section: Introductionsupporting
confidence: 78%
“…Less than 50% of caregivers (42%) report having been promptly identified by their GP. In only 18% of cases, the responsible GP approached the caregiver proactively 14. Qualitative interviews Wangler and Jansky conducted with 37 caregivers also stated that they initially feel an uncertainty about whether their needs and problems should be a matter for GP support.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these limitations, to the best of our knowledge, this pilot study is the first to reveal an association between family caregivers' primary care experience and their stress, using the internationally established measure as a tool for assessing the quality of primary care. Expectations are pinned on primary care providers as agents who care about the needs, wishes, and stresses of family caregivers 4 . Findings from this study, showing that focusing attention on the individual as a whole person and building provider‐patient relationships that make it easier to seek consultations when needed were associated with lower stress related to caregiving, may encourage primary care providers and stakeholders.…”
Section: Discussionmentioning
confidence: 83%
“…3 Thus, it is ideal for health care providers to consider the needs, wishes, and stress levels of family caregivers as well as the care recipients; this is especially expected in primary care. 4 Previous research has examined whether the support provided by care recipients' primary care providers can affect caregiving-specific well-being, such as caregiver stress, [5][6][7] but few have investigated the impact of caregivers' own primary care providers on their stress. Care recipients and caregivers are not always registered in the same general practice, even in countries with established gatekeeping systems, such as the United Kingdom.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation